Tumor-Suppressing STF cDNA 3 Overexpression Suppresses Renal Fibrosis by Alleviating Anoikis Resistance and Inhibiting the PI3K/Akt Pathway - Fei Xiao; Xinghong Liu; Yan Chen; Huanzi Dai (Karger Publishers, 2021)
Background: Myofibroblast (MF) activation is the key event of irreversible renal interstitial fibrosis. Anoikis resistance is the hallmark of active MFs, which is conferred by continuous activation of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/protein kinase B (Akt) pathway. Our previous study found that tumor-suppressing STF cDNA 3 (TSSC3) enhances the sensitivity of cells to anoikis via the PI3K/Akt pathway. Therefore, we hypothesized that TSSC3 might suppress renal interstitial fibrosis by inducing anoikis via the PI3K/Akt pathway. Methods: Cell anoikis was induced by the exogenous addition of RGD-containing peptides or by culturing cells in suspension. MFs were established by stimulating HK-2 renal tubular epithelial cells with transforming growth factor beta 1 (TGF-β1). Lentivirus vectors were to construct a TSSC3 overexpression cell model. The effects of TSSC3 on the anoikis, growth, migration, invasion, and contraction of MFs were determined using annexin V-fluorescein isothiocyanate assays, cell counting kit-8 assays, wound healing migration assays, matrigel invasion assays, and collagen-based contraction assays. Results: The results demonstrated that TGF-β1, simultaneous with the induction of MF differentiation, confers significant protection against anoikis-induced cell death, which could be partly reversed by treatment with the PI3K/Akt pathway inhibitor, LY294002. Moreover, overexpression of TSSC3 obviously impaired cell growth, cell migration, cell invasion, contraction, and anoikis resistance of MFs, and decreased the activity of the PI3K/Akt pathway and the production of extracellular matrix molecules, all of which could be attenuated by treatment with the PI3K/Akt pathway activator, 740Y-P. Taken together, this study suggested that TSSC3 attenuates the anoikis resistance and profibrogenic ability of TGF-β1-induced MF by regulating the PI3K-Akt pathway. Conclusion: These findings provide a biological basis for further exploration of the therapeutic significance of targeting MF via TSSC3 in renal interstitial fibrosis.